Physical fitness and its association with anthropometric parameters in medical students - Nida Nowreen,; Mudasir Bashir,; Ishtiaq Ahmad Sofi,; Sheikh Imran Sayeed, (Asian Journal of Medical Sciences, 2023)
Background: Although determined partly by genetics, physical fitness can be affected by a series of factors, such as sedentary behaviors, physical activity, and obesity. In general, medical students have considerable information about healthy lifestyle and dietary habits compared to other professional courses. Unfortunately, knowledge does not always translate into practice in terms of maintaining good health. Aims and Objectives: The study aims to assess the physical fitness and evaluate its association with body mass index (BMI) in medical students. Materials and Methods: This cross sectional was conducted in the Department of Physiology among the 1st-year students of Government Medical College, Srinagar, from December 2022 to February 2023. A total of 116 students in the age group of 18–22 years participated in the study. Descriptive data for age (years), gender height (m), and weight (Kg) were obtained and BMI was calculated. Physical fitness index (PFI) was measured using the modified Harvard step test. Results: The prevalence of overweight/obesity according to BMI was 41.3% (34.4% were overweight and 6.0% were obese). Among the participants, 81.7% of participants had a PFI of average to excellent while as 18.3% of participants had a PFI of low to poor. The study found a weak negative association (r-value=−0.07) between BMI and physical fitness, which was statistically not significant. Conclusion: The present study found a weak association between physical fitness and BMI which was statistically not significant. Although majority of students had good to excellent PFI, the prevalence of overweight and obesity was found to be quite high in them.